2020
DOI: 10.1073/pnas.2009119117
|View full text |Cite
|
Sign up to set email alerts
|

A specialized population of Periostin-expressing cardiac fibroblasts contributes to postnatal cardiomyocyte maturation and innervation

Abstract: During the postnatal period in mammals, the cardiac muscle transitions from hyperplasic to hypertrophic growth, the extracellular matrix (ECM) undergoes remodeling, and the heart loses regenerative capacity. While ECM maturation and crosstalk between cardiac fibroblasts (CFs) and cardiomyocytes (CMs) have been implicated in neonatal heart development, not much is known about specialized fibroblast heterogeneity and function in the early postnatal period. In order to better understand CF functions in heart matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…The expression of these markers must be matched with the absence of differentiation or lineage markers for other cell types, such as PDGFRβ and desmin (pericytes, smooth muscle) or CD31 and VE-cadherin (endothelial cells). In practice, these criteria are usually combined with information on cell position within the tissue, cell morphology and the expression of other context-specific markers such as CD90 (Thy-1), 68,69 transcription factor TCF21, 70,71 and possibly fibroblast-specific protein-1 (FSP-1, aka S100A4). 72 Considering the diversity of fibroblast features it is not surprising that no single, common fibroblast progenitor has been described.…”
Section: Fibronectinmentioning
confidence: 99%
“…The expression of these markers must be matched with the absence of differentiation or lineage markers for other cell types, such as PDGFRβ and desmin (pericytes, smooth muscle) or CD31 and VE-cadherin (endothelial cells). In practice, these criteria are usually combined with information on cell position within the tissue, cell morphology and the expression of other context-specific markers such as CD90 (Thy-1), 68,69 transcription factor TCF21, 70,71 and possibly fibroblast-specific protein-1 (FSP-1, aka S100A4). 72 Considering the diversity of fibroblast features it is not surprising that no single, common fibroblast progenitor has been described.…”
Section: Fibronectinmentioning
confidence: 99%
“…Fibroblasts form one of the main contributors to ECM deposition in response to cardiac injury and are therefore an important cell type in maintaining the balance between the fibrotic and regenerative injury response (Chablais & Jazwinska, 2012;Gemberling et al, 2015;Sánchez-iranzo et al, 2018). In addition, subpopulations of cardiac fibroblasts can have distinct roles in in cardiomyocyte maturation and innervation (Hortells et al, 2020). By scRNAseq analysis, we identified two distinct fibroblast cell states in the regenerating heart.…”
Section: Development • Accepted Manuscriptmentioning
confidence: 95%
“…The fibrotic scar is formed by cardiac fibroblasts that become activated to produce large amounts of extracellular matrix (ECM) components, like collagens. Cardiac fibroblasts mainly originate from the embryonic epicardium, which consists of a heterogeneous population of epithelial cells that cover the heart (Acharya et al, 2012;Cao et al, 2016;Gittenberger-de Groot et al, 1998;Hortells et al, 2020;Travers et al, 2016;Weinberger et al, 2020). During embryonic heart development a subset of epicardial cells undergoes an epithelial-to-mesenchymal transition (EMT) and migrates into the cardiac wall to give rise to a variety of cell types, which are commonly referred to as epicardial derived cells (EPDCs) and include predominantly cardiac fibroblasts and vascular support cells (Cao & Poss, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the important roles of non-myocyte populations in the maturation of cardiomyocytes. Hortells et al ( 2020 ) demonstrated that during the postnatal period in mice, periostin-expressing cardiac fibroblasts contribute to the phenotypic switch from immature cardiomyocytes to mature ones. Wang et al provided evidence that cardiac fibroblasts also undergo the phenotypic switch from neonatal to adult stage and that this switch regulates the maturation of cardiomyocytes.…”
Section: Recent Progresses On Quality Of Ipsc-derived Cells For Disease Study and Treatmentmentioning
confidence: 99%